Phytoplankton dynamics in southern Portuguese coastal lagoons during a discontinuous period of 40 years - Brito, Ana (2012)
Shallow coastal lagoons in southern Portugal, such as the Ria Formosa and Alvor, are considered to be highly important both ecologically and economically. Given the impact of phytoplankton in the ecosystem productivity, it is important to understand its dynamics and to consider them for the assessment of ecosystem health. All available phytoplankton data(chlorophyll a; selected species composition and abundance) within the period from 1967 to 2011 were compiled within the framework of a project to implement the Water Framework Directive. Chlorophyll a (chl a)measurements in Ria Formosa from 1967 to 1968, 1985 to 1986, 1991 to 1992, 2006 to 2008, and 2010 show similar monthly averages with some exceptions. In the 80’s the monthly averages were less than half of what was observed in the 60’s. In the 90’s, the chl a concentrations increased significantly and in the period from 2006 to 2010, chl a concentrations ranged between the values found in the 80’s. The decrease in chl a concentrations during the 80’s is likely to be associated with a peak in shellfish production. Shellfish production was recorded to have decreased from 1990 onwards. Chl concentrations in Ria de Alvor are found to vary within the same range as in Ria Formosa. However, data are limited and does not allow a detailed historical comparison. During the most important chl a peaks, the phytoplankton community was characterized by coastal species, such as Pseudo-nitzschia sp., which may be associated with upwelling events. This was found in Ria Formosa both in the 90’s and from 2000 onwards, as well as in the most recent data from Ria de Alvor. This clearly indicates the influence of the coastal dynamics in these lagoons. High chl outside the lagoon confirmed the influence of coastal waters. In addition, high chl concentrations were also observed at inner parts of the lagoon but not outside, suggesting the existence of an interior maximum. The community was mainly characterized by the existence of low salinity tolerant species, such as Kryptoperidinium foliaceum. Over the time intervals in this study, the 90th percentile values of chlorophyll a concentrations were 3.0 in Ria Formosa and 2.6 mg m 3 in the Ria de Alvor. In a five-fold classification of ecological quality from High to Bad, we propose chlorophyll a concentrations of 5.3 mg m 3 as a reference value, 8 mg m 3 for the boundary High/Good, and 12 mg m 3 for the boundary Good/Moderate. According to this, all water bodies were considered as in High status.